2015
DOI: 10.1287/orsc.2014.0956
|View full text |Cite
|
Sign up to set email alerts
|

Three Facets of Organizational Adaptation: Selection, Variety, and Plasticity

Abstract: W hen considering the adaptive dynamics of organizations, it is important to account for the full set of adaptive mechanisms, including not only the possibility of learning and adaptation of a given behavior but also the internal selection over some population of routines and behaviors. In developing such a conceptual framework, it is necessary to distinguish between the underlying stable roots of behavior and the possibly adaptive expression of those underlying templates. Selection occurs over expressed behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 45 publications
(68 reference statements)
1
72
0
Order By: Relevance
“…The latter stages of replication and retentionor exploitationdepend to a greater extent on backward-looking experiential mechanisms to replicate the new routines in diverse contexts and incorporate them in recurring operational activities. In addition, in recent work, Levinthal and Marino (2015) discuss a double-level selection process, in which an organization selects both at the level of broadly different classes of routines and at the level of variation in the characteristics of each selected class.…”
Section: Routine Creationmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter stages of replication and retentionor exploitationdepend to a greater extent on backward-looking experiential mechanisms to replicate the new routines in diverse contexts and incorporate them in recurring operational activities. In addition, in recent work, Levinthal and Marino (2015) discuss a double-level selection process, in which an organization selects both at the level of broadly different classes of routines and at the level of variation in the characteristics of each selected class.…”
Section: Routine Creationmentioning
confidence: 99%
“…Actors adapted to the rules and selected elements among new patterns of action. The artifacts were tested online in a trial-and-error learning process and new patterns of action were generated and selectively retained in the new routines (Pentland et al, 2012;Levinthal and Marino, 2015). Variation within a broad pattern of action was generated when the actors changed their behaviours, abandoned existing routines and found new ways of working associated with the contracts and process documentation.…”
Section: Evolutionary Processes and Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Levinthal & Posen (2007) and Levinthal & Marino (2015) have shown that adaptive learning processes may be selected against because they imply increased variability in performance as a result of the adjustments the firm will go through. Adaptive learning may lead to superior average performance in the long run but may lead to a higher variability in performance in the short run.…”
Section: Prior Literature On the Efficiency Of Selectionmentioning
confidence: 99%
“…When the 'fitness' of a practice depends on how many others have adopted this practice or on the presence of specific organizational characteristics, an inferior practice could become dominant (Wright, 1931;Maynard Smith, 1982;Arthur, 1989;Carroll & Harrison, 1994;Levinthal, 1997). Similarly, when selection operates on short-term performance, it might eliminate practices with positive long-term effects, especially in changing environments or when firms can adapt (Levins, 1968;Elster, 1979;Nelson & Winter, 1982;Levinthal & March, 1981;Levinthal & Posen, 2007;Levinthal & Marino, 2015).…”
Section: Introductionmentioning
confidence: 99%